2008
DOI: 10.1111/j.1651-2227.2008.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors associated with stress in mothers of preterm newborns

Abstract: The present findings suggest that providing mothers with the opportunity of discussing the infant's clinical state with health professionals and receiving psychological support on a regular basis may reduce stressful feelings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 14 publications
(24 reference statements)
2
34
0
1
Order By: Relevance
“…The repeated training sessions are similar to the present research, which can influence stress coping strategies in mothers. This study showed that the coping program for 4 Iran J Psychiatry Behav Sci. In Press(In Press):e11671.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The repeated training sessions are similar to the present research, which can influence stress coping strategies in mothers. This study showed that the coping program for 4 Iran J Psychiatry Behav Sci. In Press(In Press):e11671.…”
Section: Discussionmentioning
confidence: 99%
“…The brief COPE is a self-report tool, consisting of 28 questions, rated on a 4-point Likert scale, ranging from never (1) to always (4). It assesses 3 main styles of coping, including problem-focused, emotion-focused, and insufficient coping; each group of 2 questions is a subset of a 2…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Holding regular meetings with health professionals was considered an important form of providing support, besides minimizing maternal suffering and favoring mother-child interactions, reducing the risk of emotional and developmental problems in these children in the future. 15 Group session observations reveals that they also serve as a space for learning about the health conditions and care delivered to newborns, which can enhance the mother's participation in care.…”
Section: Institutional Organization and Its Relation With Family Partmentioning
confidence: 99%